Peranan Jumlah Wisatawan Asing, Nilai Tukar, dan PMDN dalam Sektor Pariwisata terhadap Pendapatan Devisa Pariwisata Indonesia - Nabila Fairuuz; Fachru Nofrian; Desmintari Desmintari (CV. Publikasi Indonesia, 2022)
Foreign exchange reserves have many indicators that affect their income, one of which is the tourism sector. The tourism sector has an important role as a source of foreign exchange reserves. Tourism activities create demand, both consumption and investment, which can increase the income of foreign exchange reserves in Indonesia. This study uses data from 1990 to 2019. The method used in this study is a multiple linear regression analysis model using the OLS method. The results of multiple linear regression analysis show that (1) there is a significant influence between the number of foreign tourists on tourism foreign exchange (2) there is a significant influence between the exchange rate on tourism foreign exchange (3) there is a significant influence between domestic investment in the hotel sector and restaurants to tourism foreign exchange.